EBM Tutorial: Formulating a Clinical Question (Out of Print) - Lauren Maggio; John Wiecha; Keven Jeffery; Mary Blanchard (Association of American Medical Colleges, 2007)
Abstract Created and maintained by the Boston University Alumni Medical Library, this web-based tutorial designed for self-study can be completed in approximately 5 minutes and can be used to support evidence-based medicine (EBM) practice and curricular components. The major educational topics addressed include the impact of the clinical question on EBM research, the key elements of a clinical question, how to form an answerable clinical question, and the role of the clinical question in the overall EBM process. Geared towards evidence-based practitioners and medical students (graduate and undergraduate), this tutorial is structured around an otitis media case. Through the step-by-step identification of the patient, intervention, comparison, and outcome (the PICO process), the case actively guides users in building an answerable clinical question. Due to the tutorial's interactive nature, users are engaged throughout and are asked to input information that is later revisited so they can note their progress. To ensure quality, the tutorial was reviewed by a family medicine physician. Links to related guides and worksheets are provided.